An integrative action research (IAR) on improve the financial closing process of NDA through standardizing financial reports - Jarabe, Justa Faith Carreon (Animo Repository, 2021)
Financial Statements of a Company especially of a government entity whether National Government, Local Government Unit, or even Government-Owned and Controlled Corporations (GOCC) should be reliable, accurate, and free from any amount of material errors. For this reason, COA, (2017) issued Circular No. 2017-004 to remind GOCCs of the deadlines of submission of Financial Statements and to implement the Philippine Public Sector Accounting Standards and the Revised Chart of Accounts. The Circular aims to align the current practice with the prevailing international standards and to enhance the QUALITY and UNIFORMITY of financial reporting by Philippine public sector entities. In line with this, this Insider Action Research Paper improved the Financial Closing Process of the National Dairy Authority (NDA) through standardizing the Financial Reports. It aims to harmonize the presentation of NDA’s Financial Statements for its four (4) Island Offices (Central Office, Mindanao Island office, Visayas Island Office, and Luzon Office) in compliance with the suggested format of COA issued Circulars and to minimize the manual computation during the preparation of Financial Reports. To understand and implement the change in the NDA the researcher together with her collaborators used Lewin’s three-stage change process to transform the old practices into new ones. Also to continually find ways to further improve the process in line with the changing needs and expectations of the internal as well as external users such as COA, the researcher, and her collaborators used the PDCA cycle in implementing the first and second cycle of this action research paper. The implemented change is for two cycles. The first cycle focuses on the standard format for the required set of quarterly Financial Statements. And the second cycle focuses on the improvement of the standard format and the additional requirement for the set of Financial Statements for yearend submission. To check the effectiveness of the proposed standard format, the researcher and her collaborators agreed to use the five (5) quality components of usability for evaluation. It evaluates the learnability, efficiency, memorability, error, and satisfaction of the users of the standard format. Also, the qualitative characteristics of financial reporting (understandability, relevance, reliability, and comparability) are used to check the quality of financial statements submitted to the COA resident auditors. The implementation of this standard format helps the accountants of the NDA’s Island Offices on their preparation of the NDA’s Financial Statements since it will automatically generate Financial Reports. It helps the users of the Financial Statements to rely on the Financial Statements and to have a better understanding of it due to its uniform presentation. Lastly, it helps the NDA in providing timely Financial Statements to its internal and external users and minimizes the risk of noncompliance to the issued Circulars. On a final note, this action research paper helps its readers to learn the process of implementing change in their organization or in their community to which they belong.